How western multinational companies (MNCs) attract post-90s knowledge workers in China - Yanming, CHEN (2022)
After 2010, China’s GDP overtakes Japan and becomes the world’s second-largest economy, which leads more and more western multinational companies (MNCs) to enter and expand their business in China. Due to differences in culture and social environment, western multinational companies face many challenges when they recruit talents in China. The Chinese government encourages factories to transform from low-level manufacturing to high-tech intelligent manufacturing, requiring a large number of knowledgeable workers to contribute. Therefore, western multinational companies (MNCs) need to formulate a set of recruitment strategies to attract Chinese post-90s knowledge workers. This dissertation uses questionnaire to investigate the factors that Chinese and western post-90s knowledge workers value differently when they choose western multinational companies (MNCs), recruitment channels preferred by Chinese post-90s knowledge workers and Chinese post-90s knowledge workers' job satisfaction with western multinational companies (MNCs). After investigation, we found a set of effective recruitment strategy. Firstly, whether Western or Chinese post-90s knowledge workers value every recruiting factor. Secondly, western multinational companies (MNCs) could simultaneously use multiple recruiting channels to enhance recruiting success rates in China. Thirdly, western multinational companies (MNCs) need to improve these motivators and hygiene factors with professional knowledge to enhance job satisfaction.